Single mode rib optical waveguide modeling techniques - Ibrahim, Mohd. Haniff; Mohd. Kassim, Norazan; Mohammad, Abu Bakar; Mohd. Supa'at, Abu Sahmah (IEEE, 2004)
In this paper, a single mode rib optical waveguide is modeled using three distinct methods which include the finite difference method (FD), effective index method (El) and two dimensional beam propagation method (2D-BPM). Starting from the fundamental equations of Maxwell’s, the functionalities of the said methods in solving the wave equation are discussed. Using a standard rib optical waveguide structure, comparisons between the methods are made in terms of normalized propagation constant values and the obtained results are shown to have a good agreement.